Evaluating GEMS HCHO Retrievals With TROPOMI Product, Pandora Observations, and GEOS‐Chem Simulations - Weitao Fu; Lei Zhu; Hyeong‐Ahn Kwon; Rokjin J. Park; Gitaek T. Lee; Isabelle DeSmedt; Song Liu; Xicheng Li; Yuyang Chen; Dongchuan Pu; Juan Li; Xiaoxing Zuo; et al. (Earth and Space Science)
Abstract Satellite column formaldehyde (HCHO) is an indicator of regional volatile organic compounds (VOC) emissions as HCHO is a short‐lived intermediate oxidation product. The Geostationary Environment Monitoring Spectrometer (GEMS), launched in 2020, is the first geostationary satellite to monitor hourly HCHO. GEMS offers unprecedented potential to reveal the diurnal variations of VOC emissions in Asia. Here, we present the first study to evaluate year‐round GEMS HCHO retrievals using TROPOMI satellite and ground‐based Pandora spectrometers. Our study shows that GEMS HCHO aligns with TROPOMI (r = 0.59–0.85; differences within 20% for most areas). Moreover, GEMS captures monthly and diurnal HCHO variations observed by Pandora spectrometers across Asia with differences overall within 15% (r ∼ 0.85). Diurnally, we find strong HCHO variations over urban areas but not in forests. During the fire season of mainland Southeast Asia, GEMS HCHO increases in the afternoon, in line with diurnal emission estimates from the Global Fire Emissions Database Version 4 with small fires (GFED4s) and GEOS‐Chem simulations. GEMS also captures the spatial patterns of fire emissions in GFED4s. GEMS HCHO shows negative bias when observing with a high (>60°) viewing zenith angle (VZA) and overly relies on model correction for observations to the north of 30°N.